Renal impairment and in-hospital adverse renal events in critically ill patients assessed by age-adapted estimated glomerular filtration rate criteria - Chong Zhang; Weiru Liang; Meng Ning; Bin Su; Tingting Guo; Kun Hu; Wei Su; Yi Chen; Wenjin Peng; Yingwu Liu (Renal Failure)
Background Impaired renal function (IRF) is associated with an elevated risk of major adverse renal events (MARE). However, the relationship between age-adapted estimated glomerular filtration rate (eGFR) criteria and in-hospital MARE has not been extensively studied in critically ill patients. Furthermore, the impact of eGFR trajectory changes on in-hospital MARE in this patient population remains underexplored.Methods In this study, we analyzed data from 7,423 critically ill patients using version 2.2 of the Medical Information Mart for Intensive Care IV database. Based on the age-adapted eGFR criteria, renal function status was classified as impaired renal function (IRF), subclinical impairment of renal function (SIRF), and normal renal function (NRF).Results There were 2,438 patients (32.8%) of in-hospital MARE. The incidence of MARE and their individual endpoint components was higher in patients with SIRF and IRF than in patients with NRF. Group-based trajectory modeling revealed that, compared with patients with other renal function status, patients with SIRF demonstrated the most significant decline in eGFR as well as the highest risk of MARE based on the results of the low-level-to-decline trajectory. Additionally, a trend toward an increased risk of MARE was observed in patients with SIRF and IRF, particularly among younger patients, when compared with those with NRF.Conclusions Critically ill patients with SIRF and IRF had an increased risk of in-hospital MARE. Patients with SIRF experienced the most notable decline in renal function during hospitalization, with the highest risk of MARE noted in this trajectory group. In addition, a trend toward an increased risk of MARE was observed in younger patients. Consequently, active monitoring and timely intervention in younger patients are imperative.